2018
DOI: 10.1002/hbm.24304
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted neural variability during propofol‐induced sedation and unconsciousness

Abstract: Variability quenching is a widespread neural phenomenon in which trial-to-trial variability (TTV) of neural activity is reduced by repeated presentations of a sensory stimulus. However, its neural mechanism and functional significance remain poorly understood. Recurrent network dynamics are suggested as a candidate mechanism of TTV, and they play a key role in consciousness. We thus asked whether the variability-quenching phenomenon is related to the level of consciousness. We hypothesized that TTV reduction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

8
1

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 95 publications
(205 reference statements)
0
32
1
Order By: Relevance
“…The decreased responsiveness to task-relevant external stimuli—seen in the decreased TTV and LZC changes—may thus be related to instability in the spontaneous activity during the stimulus period. This can be seen in the increased FS and PS; TTV changes are theorized to have the purpose of changing ongoing spontaneous activity as a way to increase the signal-to-noise ratio in favor of the stimulus (26, 27, 29, 82, 84). Further support for this is the correlation of TTV with both FS and PS in alpha and theta.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased responsiveness to task-relevant external stimuli—seen in the decreased TTV and LZC changes—may thus be related to instability in the spontaneous activity during the stimulus period. This can be seen in the increased FS and PS; TTV changes are theorized to have the purpose of changing ongoing spontaneous activity as a way to increase the signal-to-noise ratio in favor of the stimulus (26, 27, 29, 82, 84). Further support for this is the correlation of TTV with both FS and PS in alpha and theta.…”
Section: Discussionmentioning
confidence: 99%
“…To account for the multiple correlations performed in this study, the Benjamini-Hochberg False Discovery Rate (FDR) (Benjamini & Hochberg, 1995) was applied to all p-values, as was done in recent articles (Arazi et al, 2017;Cruzat et al, 2018;Huang et al, 2018). All statistical tests from the study were listed together and the FDR was applied to all p-values at once.…”
Section: Exact Low-resolution Brain Electromagnetic Tomography Analmentioning
confidence: 99%
“…In terms of the response amplitude, low prestimulus activity levels lead to relatively higher poststimulus activity levels than high prestimulus activity levels [ 84 , 85 , 87 ]. Importantly, recent studies in MEG [ 72 , 73 ] and fMRI [ 87 ] demonstrate that prestimulus variance and its nonadditive impact on poststimulus amplitude and variance are related to conscious contents [ 70 , 72 , 73 , 88 ] and the level and state of consciousness [ 87 ]. Most interestingly, a recent study demonstrated that prepoststimulus variance changes are accompanied by the Lempel–Zev complexity (LZC) in the prestimulus interval [ 89 , 90 ].…”
Section: Functor Natural Transformation and Consciousnessmentioning
confidence: 99%